2017
DOI: 10.1007/978-3-319-57379-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chaperones in Neurodegenerative Diseases: A Short Review

Abstract: Stress and misfolded proteins result to dysfunction in the cell, often leading to neurodegenerative diseases and aging. Misfolded proteins form toxic aggregates that threaten cell's stability and normal functions. In order to restore its homeostasis, the cell activates the UPR system. Leading role in the restoration play the molecular chaperones which target the misfolded proteins with the purpose of either helping them to unfold and refold to their natural state or lead them degradation. This paper aims to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Our results show that a dysfunction of the proteostasis system is implicated in the etiology of a series of highly prevalent psychiatric and neurodegenerative processes such as PD, dementia, and schizophrenia, among others [ 12 ]. Indeed, proteostasis alterations in the prefrontal cortex implicate proteome instability and accumulation of misfolded proteins [ 45 , 47 , 49 , 76 ] that could lead to detrimental behavioral and emotional functions in neuropsychiatric disorders [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that a dysfunction of the proteostasis system is implicated in the etiology of a series of highly prevalent psychiatric and neurodegenerative processes such as PD, dementia, and schizophrenia, among others [ 12 ]. Indeed, proteostasis alterations in the prefrontal cortex implicate proteome instability and accumulation of misfolded proteins [ 45 , 47 , 49 , 76 ] that could lead to detrimental behavioral and emotional functions in neuropsychiatric disorders [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preserving proteostasis, that is, stable conditions during processes such as biogenesis, folding, trafficking, or degradation of proteins, is crucial to guaranteeing cell functions and the ability to elaborate pertinent reactions to tissue-specific chronic and acute stressors [ 11 ]. Dysregulation of the conservative mechanisms of proteostasis involves processes that are fundamental for the viability of postmitotic cells such as neurons and has been associated with several neurodegenerative diseases, such as AD, PD, and HD, among others [ 12 ]. Thereby, with increasing knowledge about changes in the tissue protein distribution, new pathogenic mechanisms could be revealed as potential therapeutic targets, especially in the study of the ubiquitin-proteasome system and molecular chaperones [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that they are involved in the negative regulation to form aberrant, solid-like stress granules (Mateju et al, 2017). Molecular chaperone disorders usually induce toxic misfolded protein aggregates, which are more common in neurodegenerative diseases (Bobori, Theocharopoulou, & Vlamos, 2017;Qamar et al, 2018), but their link to cancer-related phase separation is only beginning to be understood.…”
Section: Interfering With Phase Separation-associated Client Moleculesmentioning
confidence: 99%
“…Via interactions with co-chaperones that regulate their localization and function, members of the Hsp70 (also known as Hspa) family of chaperones use the energy derived from ATP hydrolysis to maintain proper folding and/or turnover of synaptic proteins, and thereby, synaptic integrity (reviewed by Gorenberg and Chandra (2017)). As such, dysfunction of Hsp70 and other chaperone protein families has been implicated in several neurodegenerative diseases (for reviews see Kampinga and Bergink (2016), Ebrahimi-Fakhari et al (2011), Bobori et al (2017; Roodveldt et al (2017) and Lackie et al (2017)). Members of the Hsp70 family identified in the PANTHER pathway Parkinson disease were also identified in our cross-analysis with susceptibility genes associated with schizophrenia and ASD ( Fig.…”
Section: Panx1 Interacting Proteins In Neurodegenerative Diseases: a mentioning
confidence: 99%